The Relationship between electronic screen exposure and risk of autistic-like symptom among typically developing toddlers / Dhania Sorfina Md Zaki Fadzil and Mohd Suleiman Murad - Md Zaki Fadzil, Dhania Sorfina; Murad, Mohd Suleiman (Faculty of Health Sciences, Universiti Teknologi MARA, 2020)
This study was conducted to investigate the relationship between electronic screen exposure and risk of autistic-like symptoms in typically developing toddlers. M-CHAT-R and a demographic questionnaire were used in this cross-sectional study involving 120 parents with typically developing toddlers. Daily duration of electronic screen media viewing and presence of parent-child interaction during exposure to electronic screen media, were significantly related to risk of autistic-like symptoms among typically developing toddlers, with (p = 0.033) and (p = 0.0012) respectively. The present study revealed a relationship between electronic screen exposure and risk of autistic-like symptoms in typically developing toddlers. Future efforts should emphasize on increased awareness on the potential harm electronic screen exposure and measures to reduce high prevalence of ASD among this group. This vital to maintain their health status and avoid harmful consequences on their overall development.